(untitled) (The Research of Medical Science Review, 2024)
This paper explores the various challenges faced in the treatment of substance use disorders from a healthcare perspective. It examines factors such as stigma, access to care, and the complexities of co-occurring mental health conditions that complicate treatment efforts. Through a review of existing literature and case studies, the study identifies barriers to effective intervention, including insufficient resources, fragmented healthcare systems, and the need for specialized training among healthcare providers. The findings underscore the importance of integrated care approaches and the need for policies that promote accessibility and support for individuals struggling with substance use disorders. Ultimately, the research advocates for a holistic and collaborative framework to enhance treatment outcomes and improve the overall quality of care.